Stik Pisang Sebagai Produk Olahan Untuk Meningkatkan Nilai Tambah - Fitriasari, Pipin; Apo Sania; Ayudian Lestari Sadawa; Nurul Hasanah; Nur Cahaya Maulidah (Scimadly Publishing, 2024)
This training activity was carried out on PKK mothers in Damai Bahagia Village. The selection of PKK mothers was carried out based on the results of surveys and observations in Damai Bahagia Village, and set a target activity to conduct training on processing bananas into banana sticks. The problem faced is that bananas have not been processed into one of the leading products of MSMEs managed by PKK mothers and do not understand the calculation of cost of goods sold. Therefore, we provide training and assistance in processing banana sticks so as to increase income. The results of the training activities were in the form of various banana stick products and determination of cost of goods sold.